KATA AKRONIM DALAM BAHASA LISAN MASYARAKAT DESA BOJONGKAPOL KECAMATAN BOJONGGABIR KABUPATEN TASIKMALAYA - Sanjaya, Erwin (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2017)
This research has a broad background, knowledge about the language of the Bojongkapol village District Bojonggambir Tasikmalaya District. because researchers have a purpose to analyze the words that are in Bojongkapol village District Bojonggambir Tasikmalaya District. (1) indicates the abbrevation that is on Bojongkapol village District Bojonggambir Tasikmalaya District. (2) us of sundanese language in society Bojongkapol village District Bojonggambir Tasikmalaya District. (3) describes the word acronym in Bojongkapol village District Bojonggambir Tasikmalaya District. The method used in this research is qualitative method to describe the word learned and techniques to collect data in a way, observations, recording, and intuitive. Bojongkapol village District Bojonggambir Tasikmalaya District. Bojongkapol village District Bojonggambir Tasikmalaya District. Based on research results there are 70 word obtained in the Bojongkapol village District Bojonggambir Tasikmalaya District.it is grouped into three kinds of abbreviations, 2 word acronyms, 15 word contraction, and 53 word preosiopsis. Based on the result of the term abbreviated word obtained in Bojongkapol village District Bojonggambir Tasikmalaya District. research has benefitst for language especially word abbreviation in Bojongkapol village District Bojonggambir Tasikmalaya District.